An Exploration of the Relationship Between Promotion Strategy, Product Quality, and Service Quality on Customer Satisfaction on the Purchase of Honda Motorcycles in Pekanbaru - Surya Safari; Layla Hafni; Yosep Yosep; Sri Indrastuti; Mustafa Kamal (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study aims to determine the effects of promotional strategies, product quality, and customer service on customer satisfaction in purchasing Honda motorcycles in Pekanbaru. Research Methodology: This study used a quantitative approach with an online questionnaire survey. The measurement scale used a Likert scale. Data analysis was performed using multiple linear tests. The SPSS 21.0 application program was used. Results: A total of 100 respondents, who were customers of Honda dealers in Pekanbaru, participated in the study. The analysis revealed that promotional strategies, product quality, and customer service positively influenced customer satisfaction. Conclusions: Personal financial management is crucial for maintaining financial stability in KIP students at the Faculty of Economics and Business. Social pressures and a consumerist lifestyle must be addressed to ensure that KIP Kuliah FEB utilize their scholarships optimally Limitations: The study is limited by the sample size, as it only includes 100 respondents from one region, which may not fully represent the broader population of the country. Contributions: The findings of this study provide valuable insights for companies seeking to enhance customer satisfaction. They contribute to marketing decisions by emphasizing the need for effective promotional strategies, product quality improvements, and excellent customer service to increase consumer satisfaction.